1992
DOI: 10.1101/gad.6.4.642
|View full text |Cite
|
Sign up to set email alerts
|

Control of c-myc mRNA half-life in vitro by a protein capable of binding to a coding region stability determinant.

Abstract: Polysome-associated c-tnyc mRNA is degraded relatively rapidly in cells and in an in vitro mRNA decay system containing extracts from cultured mammalian cells. Using this system, a competition/screening assay was devised to search for factors that bind to specific regions of polysome-associated c-myc mRNA and thereby alter its half-life. mRNA stability was first assayed in reactions containing exogenous competitor RNAs corresponding to portions of c-myc mRNA itself. The addition of a 182-nucleotide sense stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
240
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(249 citation statements)
references
References 54 publications
7
240
0
2
Order By: Relevance
“…A PCR fragment containing the T7 promoter placed upstream of the c-myc coding region instability determinant was amplified as previously described 1 and used for the in vitro transcription of the target c-myc RNA region. In a final volume of 10 l, 100 to 300 attomol of radiolabeled RNA (2 nCi) were incubated with 0.5 to 2 nM of recombinant IMP-1 for 20 min at 30°C in 20 mM Tris-HCl (pH 8.0), 150 mM KCl, 2 mM MgCl 2 , 5% glycerol, 0.01% Triton X-100, 0.004% bromophenol blue and 0.1 g/ l Escherichia coli tRNA.…”
Section: Electrophoretic Mobility-shift Analysis Of Recombinant Hcrd-mentioning
confidence: 99%
See 1 more Smart Citation
“…A PCR fragment containing the T7 promoter placed upstream of the c-myc coding region instability determinant was amplified as previously described 1 and used for the in vitro transcription of the target c-myc RNA region. In a final volume of 10 l, 100 to 300 attomol of radiolabeled RNA (2 nCi) were incubated with 0.5 to 2 nM of recombinant IMP-1 for 20 min at 30°C in 20 mM Tris-HCl (pH 8.0), 150 mM KCl, 2 mM MgCl 2 , 5% glycerol, 0.01% Triton X-100, 0.004% bromophenol blue and 0.1 g/ l Escherichia coli tRNA.…”
Section: Electrophoretic Mobility-shift Analysis Of Recombinant Hcrd-mentioning
confidence: 99%
“…1,2 Disruption of the interaction between CRD-BP and the coding region instability determinant in vivo results in c-myc downregulation and, consequently, inhibition of cell growth. 3 In rat and mouse, CRD-BP protein expression is restricted to fetal and neonatal tissues.…”
mentioning
confidence: 99%
“…Two distinct c-myc half-life determinants were identi®ed. One is an AU-rich sequence in the 3'-UTR; the other is an approximately 180 nucleotide (nt), purine-rich sequence located at approximately nts 1705 ± 1886 in the coding region and encoding 60 amino acids at the protein carboxy terminus (Bernstein et al, 1992;Bonnieu et al, 1990;Herrick and Ross, 1994;Jones and Cole, 1987;Lachman et al, 1986;Wisdom andLee, 1990, 1991;Yeilding et al, 1996). We refer to this region as the Coding Region mRNA stability Determinant or CRD.…”
Section: Introductionmentioning
confidence: 99%
“…Two observations suggested that the CRD is a site for binding of a speci®c protein, the Coding Region Determinant-Binding Protein (CRD-BP) which, when bound to the CRD, protects the CRD from attack by an endonuclease. First, when synthetic competitor CRD RNA was added to the reactions, cmyc mRNA was speci®cally destabilized eightfold (Bernstein et al, 1992). In the presence of the competitor, but not in its absence, a decay product resulting from endonucleolytic attack within the CRD was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The specific regions that the mRNA binding proteins interact with may be localized either on the 5′ untranslated region, the coding region or the 3′ untranslated region of the mRNA (Ross 1995). c-Fos, c-Myc, tropoelastin, thymidylate synthase and dihydrofolate reductase are some of the RNAs having regulatory elements for trans-acting factors in the coding region (Bernstein, et al 1992, Chen, et al 1992, Lemm, et al 2002, Prokipcak, et al 1994, Shyu, et al 1991, Shyu, et al 1989, Zang, et al 1999. In general, the steady state levels of the mRNA expression are regulated by either increasing or decreasing the degradation rate resulting from the interaction with specific RNA binding proteins.…”
Section: Accelerated Lh Receptor Mrna Degradation As a Regulatory Mecmentioning
confidence: 99%